Lesson Planning With Engagement in Mind: Proactive Classroom Management Strategies for Curriculum Instruction. (January 2019) - Nagro, Sarah A.; Fraser, Dawn W.; Hooks, Sara D.
Teacher success is critical to student success, yet teachers are challenged daily to meet their students' diverse learning and behavioral needs. Of major concern is the time many teachers spend managing student behaviors, which takes time away from instruction. One way to reduce time spent managing student behavior and increase student engagement is to use proactive classroom management strategies. Teachers can embed proactive research-based strategies within their lesson plans to reduce behavior problems and improve achievement for all students, including students with disabilities. This article highlights four research-based proactive strategy categories including whole-group response systems, movement integration, visual supports, and student choice. This article illustrates how teachers can embed strategies from these categories in their lesson planning and includes a lesson plan template with teacher-created examples.